IMPROVING WORK EFFECTIVENESS THROUGH COMPETENCE - Wiwin Sapta Prabudi; Kiki Farida Ferine; Sri Rahayu (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
This study aims to analyze the influence of career management, organizational commitment, and competence on work effectiveness, as well as examining the moderating role of competence. A quantitative approach was applied using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to 86 employee respondents. The results indicate that career management, organizational commitment, and competence have a positive and significant effect on work effectiveness. However, competence does not significantly moderate the relationship between career management or organizational commitment and work effectiveness. These findings highlight the importance of strengthening career management and enhancing organizational commitment to improve employee work effectiveness.